Implementasi Model PBL, NHT dan Make a Match Meningkatkan Hasil Belajar Bahasa Indonesia Membaca Pemahaman Di Sekolah Dasar - Mir’atur Rahmah; Susilawaty (Jurnal Pendidikan Sosial Dan Konseling, 2024)
The problem in this research is that the learning outcomes of grade 5 students including Indonesian language material are low. This problem is solved using the Problem Based Learning, Number Head Together, and Make a Match learning models. This research aims to improve learning outcomes. The research uses classroom action research. The forms of research data are qualitative and quantitative data. Qualitative data was obtained from observing teacher and student activities. Quantitative is obtained through worksheets and student group assessments. Based on the findings, teacher activity increased to a score of 32 with a very good standard. Student activity at meetings 1-3 continues to increase until the very active standard is reached. Therefore, this influences learning outcomes at each meeting to continue to increase until they reach 100%. Based on the findings, it was concluded that learning using the Problem Based Learning, Number Head Together, and Make a Match learning models improved student learning outcomes.